To evaluate the profile of patients with disc edema/ papilledema and their presenting pattern - Meena, Vandana; Sharma, Unnati (International Journal of Medical Research and Review, 2016)
Background: Raised intracranial pressure (ICP) is a potentially life threatening condition, which can also lead to visual loss and blindness. One of the only objective signs accessible during physical examination to confirm a suspicion of raised ICP is papilledema, or swelling of the optic nerve head (ONH). Material & Methods: The present study is a non randomized prospective case series being conducted in the 50 patients with disc edema/papilledema attending OPD and referred from other departments to DEPARTMENT OF OPHTHALMOLOGY, Gandhi Medical College and associated Hamidia Hospital, Bhopal from January 2013- December 2014. All patients underwent a complete medical evaluation including careful history taking, ophthalmic examination, complete blood count, blood sugar,urea,creatinine, serum lipid profile, thyroid, chest x-ray in specific cases. and CSF analysis (including opening pressure), follow up examination was compared with fundal photography. Results: In our study out of 50 patients, Most commonly affected age group was between 21-30 years in which 32% cases were observed, 42% affected were males and 58% females. Papilledema in 30% patient were of local cause in which 22% cases were of optic neuropathy followed by 6% cases of AION in age group of 51-60 year followed by 2% cases of BRAO in age group of 41-40 years. Among systemic causes, 24% cases of ICSOL followed by 12% cases of meningitis, 10% cases of malignant hypertension, 8% cases of drug history, 6% cases of malaria and 2% case each of diabetes, pseudotumorcerebri, anaemia, encephalopathy and head injury. Conclusion: ophthalmic evaluation and subjective grading of papilledema by FUNDAL examination has the potential of being a low cost objectively and quantitatively, and assess progression and efficacy of treatment directed toward lowering ICP and thus improve clinical decision-making regarding its diagnosis and treatment papilledema.